Sistem Manajemen Keanggotaan Pelanggan pada Usaha Kuliner Berbasis Mobile Menggunakan Metode RAD - Ricky Riotaro; Rezki Kurniati (STIKes Ibnu Sina Ajibarang, 2025)
Bos Salad Bengkalis is a culinary company that offers healthy and fresh salads. With rapid business growth, managing customer data, reward programs, and transactions is becoming increasingly important. For this reason, a Mobile-based membership management system is needed that can improve customer experience by creating a Reward program, then to facilitate management and customer transaction data, a Website-based system is also made for the admin. This research aims to design and develop an effective and efficient customer membership management system using the Rapid Application Development (RAD) method. This method was chosen because it allows rapid and orderly development, so that the system built can meet the needs. The main features to be developed include member registration, member profile management, point and reward system, and transaction management. Through the implementation of this system, Bos Salad Bengkalis can obtain more accurate data on customer behavior and preferences. Thus, the development of this membership management system is a strategic step for Bos Salad Bengkalis in facing challenges and taking advantage of opportunities in today's digital era.